3D-Simulations of Transverse Optical Modes of the Free Electron Laser Resonator with Hole Output Coupling (Communications in Computational Physics, 2006)
The transverse construction of optical modes in the wiggler is calculated andthe numerical simulations of the free-electron laser hole-coupled resonator are carriedout. These 3D-simulations include optical amplitude distributions, modes evolvementof optical field and the influence of hole-radius on the distributing of modes. The numerical simulations confirm that the fraction of the even-order modes increase in thestart-up stage and then decreases in the exponential gain stage. Moreover, it is foundthat the fundamental mode is dominant in the saturate stage. Based on this observation, we estimate the optical output coupling by using the the fundamental mode. It isfound that the numerical results and the first-order estimate are in good agreement fora range of the hole size.